International Reserve Trends in the South Caucasus and Central Asia Region - Floerkemeier, Holger (IMF Working Papers; Working Paper ;, 2008)
In recent years, the South Caucasus and Central Asia countries (CCA-6) have received significant foreign exchange inflows. While a healthy reserve buffer is desirable to selfinsure against external crises, holding international reserves also involves costs. We analyze the adequacy of CCA-6 reserves using widely recognized rules of thumb, and simulate optimal reserve levels applying the Jeanne (2007) model. Both the adequacy measures and the model-based simulations indicate that, with the exception of Tajikistan, CCA-6 reserves had increased to broadly comfortable levels by 2006. More recently, reserve adequacy has been tested in Kazakhstan, which has been affected by the 2007 global liquidity crunch.